Lexical Markers of Regional History (Podillia, Ukraine) - Marchyshyna, Alla; Skrypnyk, Anatolii (Acta humanitarica academiae Saulensis, 2026)
The paper considers linguistic mirroring of the regional history of Podillia in Mid-Western Ukraine. The territory now termed as Podillia (Ukrainian поділ – lowland, plain) is situated on the crossroads of trade, military, religious, cultural, ethnic routes the intertwining of which affected the local placenames and speech. Mostly, the centre of Podillia – the town of Kamianets-Podilskyi – reflected and preserved the eventful past and kept the memories of the years gone by. The historic events, processes, policies, transformations the region went through left their traces in the landmarks which are still in use today, these refer to the names of villages (Мукарів Татарський / Mukariv Tatarskyi, Татаринці / Tataryntsi), town streets and districts (Вулиця Князів Коріатовичів / Vulytsia Kniaziv Koriatovychiv – Karijotaičiai; Вулиця Татарська ‘Tatarska Street’; ринок / rynok (Rynek), its suburbs (Каравсари / Karvasary ‘Caravanserai’). There are numerous lexemes in the local speech which appeared after the invasions, close contacts with other peoples, partitions of the countries, state treaties, political contracts, etc. These lingual units bear the national colouring of the source language and decorate the local speech of Podillia dwellers making it peculiar and recognizable due to the historic past our region went through. The paper is an attempt to analyze and systematize the etymology of linguistic signs, the reasons and nature of borrowings, the causes and logic of nominations and their value for the further generations of Podollians.
Keywords: Podillia; regional history; placename; landmark; local speech; lexical unit; etymology